Korelasi Shared Leadership dan Perilaku Inovatif Serta Kontribusinya Untuk Peningkatan Kinerja Karyawan Bank: Correlation of Shared Leadership And Innovative Behavior and Its Contribution To Improving Bank Employee Performance - Sondari Gadzali, Silvy; Kartini, Titin (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Several previous studies have argued that the concept of shared leadership is directly related to the leadership style adopted in an organisation, which is a cohesive style and strategy for teamwork that leads to good business performance in many industries. This research examines the relationship between different leadership styles and innovative work behaviour (IWB) which will ultimately lead to improved performance of bank employees. This quantitative research, which in its analysis employs multiple linear regression formula. Thus, this study examines the operational framework of different leadership styles and the influence of IWB on employee work. This study found that leadership styles, transformational leadership, individual empowerment leadership (IEL), team empowerment leadership, and participative leadership (PL) are strategically applied for the improvement of employee cooperation, but IEL and PL are more strategic and performance-enhancing on employees' Innovative work behaviour (IWB). The conclusions of the research show that the shared leadership style has the potential to build PL and IEL in an effort to improve and explain in more detail the theory of leadership styles in teams in organizations. Keywords: shared leadership, individual empowerment leadership, team empowerment leadership, participative leadership, innovative work behaviour